Sustainable Nature Tourism Development at Katobung Waterfall: Implications for Local Economic Development and Environmental Conservation - Maisyah Khairani Hasibuan; Yusrizal; Ahmad Syakir (Jurnal Investasi Islam, 2026)
This study aims to analyze the impact of the Katobung Waterfall development on the community's microeconomics and regional finances, as well as identify structural constraints to its management in a state forest area. Using a qualitative approach with a phenomenological design, data were collected through in-depth interviews with 12 key informants and field observations. Data analysis employed a modified Moustakas method through the stages of horizontalization and clustering themes using the Common-Pool Resources Theory and Livelihood Framework analysis tools. Field findings indicate that self-help tourism has triggered a diversification of food stall income of Rp150,000 to Rp200,000 every weekend and reduced unemployment through informal transportation services. However, its macro contribution to Regional Original Income (PAD) is zero due to a regulatory void. The local government is hampered in allocating APBD funds for repairs to a 14-kilometer road and sanitation because the location is in a Production Forest area under the auspices of the KPHP. This institutional friction has triggered illegal management, parking conflicts, and garbage accumulation. This research provides a scientific contribution in the form of an antithesis to the classical CBT theory by proving that local control without formal legal certainty and adequate human capital actually traps destinations in the Tragedy of the Commons, thus requiring a Collaborative Sustainable Governance framework.